Pertanggungjawaban Perbankan Dalam Melindungi Data Pribadi Nasabah Akibat Peretasan Studi Kasus Bank Syariah Indonesia - Trianda Lestari; Syahrando Muhti; Reky Yuliansyah (Lembaga Pengembangan Kinerja Dosen, 2024)
BSI is one of the banks that experienced hacking and attacks from irresponsible parties. Lockbit threatened BSI to immediately contact him to carry out negotiations regarding 1.5 TB of customer data which was threatened with being disseminated if BSI did not fulfill its request by the specified time limit. given. In the end, this happened because the given time limit had passed, there was a lockbit post showing a link connected to banking data. This case has certainly become the center of attention, because BSI is still reluctant to provide further information regarding customer data leaks and personal data protection has not been provided. This research method uses a normative legal method which refers to statutory regulations and related sources. The legal theory used is the theory of legal certainty, to see how certain banks provide responsibility for protecting customers' personal data as regulated in banking law. So researchers can also find the title in the article entitled Banking Responsibility in protecting personal data of bank customers due to hacking BSI case study